2018
DOI: 10.1002/jso.24968
|View full text |Cite
|
Sign up to set email alerts
|

Development and prospective validation of a model estimating risk of readmission in cancer patients

Abstract: An unplanned readmission risk model developed specifically for cancer patients performs well when validated prospectively. The specificity of the model for cancer patients, EMR incorporation, and prospective validation justify use of the model in future studies designed to reduce and prevent readmissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Studies have identified many risk factors for hospital readmission within 30 days, including age, race, lack of a regular health care provider, major surgery, medical comorbidities, length of hospital stay, previous admission(s) in the past year, failure to transfer critical information to the outpatient setting, premature hospital discharge, and the higher number of medications prescribed at hospital discharge. [4][5][6][7] Newer readmission risk models, such as the cancer specific model developed by Schmidt and colleagues 8 have acceptable predictive ability (C statistic = 0.70) and are superior to the clinical judgement of health care providers in identifying patients at the highest risk of hospital readmission. 8,9 General-purpose hospital readmission risk assessment models are diverse, ranging from in depth multidisciplinary patient interviews to more simplistic screening tool using a few variables.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have identified many risk factors for hospital readmission within 30 days, including age, race, lack of a regular health care provider, major surgery, medical comorbidities, length of hospital stay, previous admission(s) in the past year, failure to transfer critical information to the outpatient setting, premature hospital discharge, and the higher number of medications prescribed at hospital discharge. [4][5][6][7] Newer readmission risk models, such as the cancer specific model developed by Schmidt and colleagues 8 have acceptable predictive ability (C statistic = 0.70) and are superior to the clinical judgement of health care providers in identifying patients at the highest risk of hospital readmission. 8,9 General-purpose hospital readmission risk assessment models are diverse, ranging from in depth multidisciplinary patient interviews to more simplistic screening tool using a few variables.…”
mentioning
confidence: 99%
“…[4][5][6][7] Newer readmission risk models, such as the cancer specific model developed by Schmidt and colleagues 8 have acceptable predictive ability (C statistic = 0.70) and are superior to the clinical judgement of health care providers in identifying patients at the highest risk of hospital readmission. 8,9 General-purpose hospital readmission risk assessment models are diverse, ranging from in depth multidisciplinary patient interviews to more simplistic screening tool using a few variables. 6,[10][11][12] These risk assessment models use factors such as illness severity, hospitalization in the past year, emergency department visits, age, ethnicity, and socioeconomic status to predict hospital readmissions.…”
mentioning
confidence: 99%
“…A few studies have been conducted to identify the likelihood of unplanned readmission and the associated risk factors in general medicine and a variety of specialties. 13 , 20 , 21 , 23 - 34 With the advancement of artificial intelligence and computational technologies, more complex algorithms can be used, and the predictions become more individualized. For instance, using deep learning on a rich set of EHRs, Rajkomar et al 32 achieved approximately 10% AUROC improvement in predicting 30-day unplanned readmission at discharge than traditional approaches.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent work using explainable gradient-boosted trees approach also achieved similar performance, with an AUROC of 0.76 and the ability to generate personalized predictions. 13 For oncological models, Schmidt et al 21 were the first to develop a statistical model using logistic regression with validation c-statistics of 0.70. However, the prospective analysis was descriptive, and no prospective predictive performance was reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation